Hepatoprotective effect of coffee pulp aqueous extract combined with simvastatin against hepatic steatosis in high-fat diet-induced obese rats - Atcharaporn Ontawong (2019)
© 2019 Elsevier Ltd This study investigated the effect of coffee pulp aqueous extract (CPE) on obesity- induced hepatic steatosis in rats and the mechanism involved. Male Wistar rats were fed high-fat diet for 12 weeks and supplemented with 1000 mg/kg BW CPE or 40 mg/kg BW simvastatin or CPE combined with 20 mg/kg BW simvastatin for another 12 weeks. The lipid profiles, presence of insulin resistance, development of hepatic steatosis and related mechanisms were investigated. Results show that CPE, simvastatin and combined treatment improved lipid profiles, insulin resistance, oxidative stress and hepatic steatosis. Correspondingly, CPE induced the lipolytic gene PPARα while combination treatment additively suppressed the lipogenic genes PPARγ and SREBP1-c. Such effects downregulated the fatty acid transporter FAT/CD36, and activated AMPK, which concomitantly improved obese induced-hepatic steatosis. Collectively, hepato-protective effects of CPE, particularly combined with simvastatin, could broaden the therapeutic options for hyperlipidaemia and NAFLD patients who receive lipid-lowering drugs.